A simple and effective process for recycling zinc-rich paint residue. (June 2018) - Xing, Peng; Ma, Baozhong; Wang, Chengyan; Wang, Ling; Chen, Yongqiang
Graphical abstract: Highlights: Oxidative alkaline leaching-electrowinning was developed for the recovery of zinc. Air introduction significantly facilitated the leaching of zinc in ZPR. ZRPs before and after leaching were characterized by XRD. The process parameters of electrowinning were optimized. Thermal analysis of depleted leaching residue was carried out. Abstract: Continuous growth of the shipping industry and infrastructure has consumed large amounts of zinc-rich paint (ZP) for the protection of steel structures against corrosion. Consequently, a growing amount of waste zinc-rich paint residue (ZPR) is being generated from anticorrosion spraying. ZPR is classified as hazardous waste in most industrialized countries, but it contains considerable amounts of organic compounds with high calorific value and zinc species that can potentially be recycled. Most of the ZPR generated is not properly treated, and this study presents a simple and efficient process for recycling ZPR. The zinc in ZPR was recovered via a hydrometallurgical route through oxidative alkaline leaching and electrowinning. The results show that the leaching ratio of zinc was greater than 98% at 95 °C, NaOH concentration of 250 g/L, liquid/solid ratio of 10:1, air flow rate of 0.6 L/min, and leaching time of 1.5 h. The appropriate minimum concentration of zinc for electrowinning was determined to be 10 g/L. Adding 50 mg/L of gelatin to the electrolyte significantly refined the grain and the optimum current density was determined to be 200 A/m 2 . Fern shaped cathode zinc powders with a purity of 99.8% were obtained. A high current efficiency (92.7%) was also obtained with energy consumption of 2330.3 kWh per ton of zinc produced. The composition and thermal analysis of the leaching residue suggest that co-processing in cement kiln may be suitable for disposing the leaching residue of ZPR. The experimental results show that the proposed process is promising for ZPR recycling.